Identifikasi Keluhan Kesehatan Mahasiswa Selama Perkuliahan Daring pada Masa Pandemic Covid19: Identification of Student Health Complaints During Online Lectures on the Covid19 Pandemic Period - Sobirin, Mohammad (Jurnal Surya Medika (JSM), 2020)
Students are the main factor that determines lecture activities run properly. The long learning process makes students experience many difficulties. With the online lecture as a result of the Covid19 pandemic, it is possible for student discomfort during lectures to increase. In this study, an identification was made related to health complaints that occur in students during lectures using the online method. The research method is to use descriptive methods from statistical calculations and the NBM (Nordic Body Map) questionnaire. Data collection was carried out on 30 students at the Institut Teknologi dan Sains Nahdlatul Ulama Pekalongan. The results of the analysis showed that health complaints occurred in the form of temporary pain, longevity, and permanence. The most painful body points are located in the area of the hands (shoulders, upper arms, forearms, and wrists), and the trunk (neck, back, hips, waist, and buttocks). Based on these results a solution is needed in the form of good posture at work, and the use of work tools and appropriate supporting media.